Inside a thug's heart : with original poems and letters by Tupac Shakur - Ardis, Angela (New York : Dafina Books, 2004)
Details the daily exchange and special bond between the author and Tupac Shakur, which commenced during his stay at Riker's Island, in this powerful collection of personal letters, original poems, and intimate conversations that provides rare insight into the thoughts and aspirations of this musical icon.
Bet -- Call -- First letter exchange -- Tupac reaches out -- Our letters cross -- Misunderstood -- Request -- Getting personal (and shocked) -- Trying to get to the bottom of it -- Invitation -- Thug mansion -- Getting really personal -- Getting heavier -- Anticipation -- He truly needed a hug -- I send an invitation -- Another shocking discovery -- Trip -- Visit -- Release.
Keywords: Shakur, Tupac, -- 1971-1996 -- Correspondence; Shakur, Tupac, -- 1971-1996 -- Imprisonment; African American poets -- Correspondence; Prisoners -- United States -- Correspondence; Rap musicians -- United States -- Correspondence